(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article discusses the rationale for the new anti-erosion technology and the design of the plow, which helps to conserve moisture and prevent water erosion on sloping lands. The objects of the study are the anti-erosion technology of ridge-step plowing and a plow for carrying out this method of tillage. A new anti-erosion technology of ridge-step plowing has been proposed, which contributes to the displacement of the soil down and up the slope, incomplete rotation of the formation alternates with full (180° within the furrow). The plow consists of stepwise arranged screw plow housings and guide plates with working surfaces facing the ploughshare surfaces of the housings. Odd-numbered hulls are equipped with short guide plates, paraglaw-type soil dredgers are installed behind even-numbered hulls. After the passage of the plow, a stepped bottom of the furrow is formed with a ridge profile of the surface of the arable land, rainwater is trapped and accumulated. The occurrence of water erosion is prevented. As a result of experimental studies, the following optimal parameters were determined: the length of the odd–case hood was 75 cm, the length of the odd–case hood was 93 cm; the longitudinal distance between the housings was 50 cm. It has been established that an effective method of ridge-step plowing of slopes is the alternation of an incomplete turn of the formation with a complete one within the furrow by 180° in combination with strip under-arable loosening. A description of the rational design scheme of a plow for a comb-step plow is given. It is noted that with a longitudinal distance of 0.5 m between the housings, the required high-quality incomplete turnover of the plates is provided with the lowest energy costs with a length of 75 cm.